2016
DOI: 10.1021/acsami.5b12186
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Conductivity and Air Stability of Al-Doped Li7La3Zr2O12 Sintered in Alumina and Pt Crucibles

Abstract: Li7La3Zr2O12 (LLZO) is a promising electrolyte material for all-solid-state battery due to its high ionic conductivity and good stability with metallic lithium. In this article, we studied the effect of crucibles on the ionic conductivity and air stability by synthesizing 0.25Al doped LLZO pellets in Pt crucibles and alumina crucibles, respectively. The results show that the composition and microstructure of the pellets play important roles influencing the ionic conductivity, relative density, and air stabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
200
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 249 publications
(210 citation statements)
references
References 43 publications
9
200
0
1
Order By: Relevance
“…Garnet-like solid electrolytes are chemically stable with Li metal and have a high electrochemical window of up to 6 V. [36][37][38][39][40][41][42][43][44][45]67] However, many studies demonstrated that LLZO is unstable in air [68][69][70][71][72] mainly because of water vapor and carbon dioxide, and thus its body integrity and ionic conductivity are considerably affected. A small amount of Li 2 CO 3 forms on the surface of www.advenergymat.de LLZO ceramics and greatly increases interfacial resistance.…”
Section: Chemical Stability Of the Solid Electrolytesmentioning
confidence: 99%
See 1 more Smart Citation
“…Garnet-like solid electrolytes are chemically stable with Li metal and have a high electrochemical window of up to 6 V. [36][37][38][39][40][41][42][43][44][45]67] However, many studies demonstrated that LLZO is unstable in air [68][69][70][71][72] mainly because of water vapor and carbon dioxide, and thus its body integrity and ionic conductivity are considerably affected. A small amount of Li 2 CO 3 forms on the surface of www.advenergymat.de LLZO ceramics and greatly increases interfacial resistance.…”
Section: Chemical Stability Of the Solid Electrolytesmentioning
confidence: 99%
“…[70] As a result, LLZO ceramic with small grain size is often preferred. However, Xia et al [71] refuted the opinion that LLZO pellets sintered in Pt crucible with large grains and reduced grain boundaries improves air stability. Consequently, the particle size should be controlled for air stability and surface treated before using LLZO pellets.…”
Section: Chemical Stability Of the Solid Electrolytesmentioning
confidence: 99%
“…Estimated lattice parameters are in agreement with the literature. 32 To understand the phase purity of the calcined LLZO polycrystalline powders (750 o C for 3 h) and the corresponding sintered LLZO pellet, unpolarized micro-Raman spectroscopic studies were conducted in the wavenumber range from 100 to 550 cm −1 . The results are plotted in Fig.…”
Section: Crystallographic Properties Related To Garnet Phase Puritymentioning
confidence: 99%
“…32 For comparison, the relative density of the pellet was also examined by the conventional Archimedes method and is almost identical to the projected value. Morphological features at fractured surface of the sintered pellet are shown in Fig.…”
Section: Crystallographic Properties Related To Garnet Phase Puritymentioning
confidence: 99%
“…48,49 Similarly, reaction with the solvent may produce ionically insulating surface layers, such as carbonates, on particles in solution, complicating subsequent sintering. [50][51][52] The successful sintering of metal oxides to high density requires control of multiple process parameters, and processes must typically be tuned to the specific compound being sintered. 53 Here, factors of importance based on LLZO are highlighted.…”
mentioning
confidence: 99%